Eutogenes frater Volgin (Acari, Cheyletidae): A New Member of the Acarofauna in Turkey - Doğan, Salih; Doğan, Sibel; Erman, Orhan (My University, 2019)
Three female mite (Acari) specimens collected from litter and soil under silverberry (Elaeagnus angustifolia) in Elazığ province, Turkey were identified as Eutogenes frater Volgin (Cheyletidae). This species shows distinct differences from other species in the genus, namely dorsal idiosoma covered by two shields, surface of the shields with papilliform granules, all dorsal setae fan-like, propodosomal shield bearing 10 pairs of setae, hysterosoma with 12 pairs of dorsal body setae. Eutogenes frater has been given before from the type locality, Bulgaria, and was later recorded from Algeria, Hungary and Iran. This species has also been known from Giza, the north of the Nile Delta (Egypt) and Burg Al Arab (United Arab Republic). Description of this species with its phase contrast and differential interference contrast (DIC) micrographs are provided here. This is the first reported occurrence of the genus Eutogenes Baker from Turkey.
Keywords: Biyoloji